Host plant nutrition drives fitness outcomes in the cactus specialist Drosophila mettleri - Lidane Noronha; Brian P. Lazzaro; Patrick M. O’Grady (PLoS ONE, 2026)
Organisms must navigate complex interactions with host plants, microbial communities, and environmental cues to ensure their survival and reproductive success when adapting to novel environments. Due to their ecological constraints, host plant specialists can be used to study how these interactions affect fitness due to their ecological constraints. In specialist species, such as cactophilic Drosophila , it remains unclear how feeding behavior, substrate composition, and microbial interactions collectively shape fitness outcomes. We examined the effects of laboratory media (cornmeal vs. banana) differing in their base diet and cactus-derived additives (dried Saguaro powder, exudate from rotting Saguaro, soil soaked by rotting Saguaro) on fitness in Drosophila mettleri , a columnar cactus specialist that breeds in Saguaro cactus ( Carnegiea gigantea ) in the Sonoran Desert. Cactus supplements often reduced survival from egg to pupa, but increased survival from pupa to adult, resulting in stage specific tradeoffs shaping egg-to-adult fitness. Results show interactions between food substrate and cactus treatment: cactus supplementation reduced survival on banana media but increased survival on cornmeal-based diets. Feeding rate and overall amount of media consumed did not differ among treatments, indicating that differences in survival and fitness may depend on the broader nutritional environment and developmental stage. This suggests that studying host specialization should include multiple life stages.